Patient education interventions for colorectal cancer patients with stoma: A systematic review. Issue 10 (October 2017) - Faury, Stéphane; Koleck, Michèle; Foucaud, Jérôme; M'Bailara, Katia; Quintard, Bruno
Highlights: First review of patient education interventions for colorectal cancer with stoma. Very few studies (N = 15) are available in this field. Patient education interventions are heterogeneous in delivery and outcomes. More quantitative research is needed to define best practices. Abstract: Objectives: To describe the various types of patient education interventions for colorectal cancer patients with stoma and to examine their effects on quality of life, psychosocial skills and self-management skills. Methods: A systematic review was performed. Six electronic databases were searched. Inclusion criteria were: studies about patient education applying quantitative methods including digestive stoma adults with colorectal cancer. The primary outcome was quality of life. Secondary outcomes were psychosocial and self-management skills. Results: Thirteen studies were identified and included. Five studies examined quality of life and three reported improvements. Patient education improved some psychosocial and self-management skills. Contrasting findings were reported for specific-disease quality of life, emotional distress, length of hospital stay, stoma complications and readmission rate. Conclusions: Patient education has a positive impact on some psychosocial and self-management skills, indicating that this area should be developed. Contrasting findings were reported for quality of life. Methodologies are heterogeneous making it difficult to produce evidence-based guidelines. This article proposes tools to carry out further studies on this subject and to improve understanding. Practice implication: Further education intervention for stoma patients with colorectal cancer should be standardized in terms of intervention, duration and outcome measures to compare intervention and determine best practice.